If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + 4w + 6 = -23 + -3w Reorder the terms: -10 + 6 + 4w = -23 + -3w Combine like terms: -10 + 6 = -4 -4 + 4w = -23 + -3w Solving -4 + 4w = -23 + -3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3w' to each side of the equation. -4 + 4w + 3w = -23 + -3w + 3w Combine like terms: 4w + 3w = 7w -4 + 7w = -23 + -3w + 3w Combine like terms: -3w + 3w = 0 -4 + 7w = -23 + 0 -4 + 7w = -23 Add '4' to each side of the equation. -4 + 4 + 7w = -23 + 4 Combine like terms: -4 + 4 = 0 0 + 7w = -23 + 4 7w = -23 + 4 Combine like terms: -23 + 4 = -19 7w = -19 Divide each side by '7'. w = -2.714285714 Simplifying w = -2.714285714
| 12/8x=7/10 | | 7a-4=4a+19 | | 9x^4-8x^2= | | 3x-11/4=-2x | | 3(5b-2)+2=26 | | 8a+3a+18=8+7a+6 | | 4=5/w-2 | | -1/9x=-3/4 | | -1=-3z+20 | | [x-3]=4x+9 | | 3(y-8)-2y=12 | | -9=r+(-2) | | 5.2/4.4 | | -4(d+12)=16 | | [-5x]=35 | | -18=3X-3 | | -29=15+y | | 6x+6(-3)=-8 | | 10q-9q=4 | | -j=-103 | | 2(3x+4)+x= | | 2-c=3 | | [-5x]=10 | | 9(2y+5)-2y-8= | | 5x^3-32x^2-21x=0 | | 8.8=x+x | | x-(-16)=-3 | | (2-w)(4w-3)=0 | | 14c-9c+5=15 | | 2(-7-8n)+(8-3n)=79 | | 6.3x-5+x-2.1= | | 8n-12+14=12n-4+4n+2 |